A new lizard of Phymaturus (Iguania: Liolaemidae) from Argentina - Lobo Gaviola, Fernando Jose (2012)
In this study, we describe a new taxon for the genus Phymaturus from the Sierra Laguna Blanca, Catamarca Province, Argentina. This area is known to be an isolated part of the Puna region where other endemic species of vertebrates occur. This new species of lizard belongs to the palluma group because it exhibits juxtaposed superciliary scales, rugose caudal scales, and typically a fragmented subocular scale. Also, this new Phymaturus is assignable, within the palluma group, to the northern or Puna clade because it presents the typical “spray” pattern and brown tails in males, which are distinct from the dorsal-reticulated pattern and yellow tails in species of the southern palluma group. It differs from its relatives in the Puna clade by having the following combination of characters: scapular spot present (more conspicuous in juveniles and females), yellow color in flank of females, males without enlarged scales on ventral surface of the base of tail, males with dark brown throat, enlarged scales on borders of posterior gular fold inconspicuous, ringed tails in both sexes, incomplete pigmentation over dorsum of neck, diffuse white transverse stripes over dorsum of body in females, absence of vertebral stripe, and in some specimens a divided rostral scale. Finally, we present new characters to be considered in future studies of Phymaturus systematics.